A extensão em educação popular na Universidade Federal da Paraíba: resgate histórico e perfil atual - Santos, Thatiane Cristina Ponciano dos (2021)
The Federal University of Paraíba, in recognition of the mission of contributing critically to the development of the theoretical-methodological perspective of Popular Education in Extension practices, creates the Coordination of Popular Education linked to the Pro-Rectory of Extension. In order to contribute to the achievement of the objectives of that unit, this research addressed the theme Extension in Popular Education at the Federal University of Paraíba, with the main aim of rescuing the history of extension in popular education at UFPB and describe the current profile of that segment of the extension in order to contribute to future actions in support of these initiatives. Specifically, the study aimed at supporting important aspects of university extension and its transformations over the years, highlighting the participation of Forproex as the main actor in the institutionalization of university extension in Brazil. The study explored authors who dialogue on the theme of popular education, with its methods and principles. This research was developed with descriptive exploratory methodology of qualitative approach and used the semi-structured interview and survey of information in documents about the extension at UFPB as instruments of data collection. After discussing the theme of extension and popular education, the research carried out a survey through documents and legislation on the institutionalization of extension at UFPB. Next, it mapped extension projects in popular education in the annals of the UFPB extension meetings between 1994 and 2016 in order to recover the historical perspective of that segment. As an instrument of data collection, semi-structured interviews were used with coordinators of significant projects from the 1990s. The instrument provided a complement to the documentary research, providing important elements of the historical process, as well as peculiarities of the projects that the documentary research did not reach. To draw a profile, a mapping of extension projects in popular education for the year 2019 was carried out by the SIGAA system in the extension module.